2016
DOI: 10.1089/jpm.2015.0325
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Advance Care Planning among African Americans: Results of a Systematic Integrated Review

Abstract: The multiple factors that impact ACP for AA are inter-related and may result in part from historical realities that shape contemporary experience. We know little from the data about how best to improve ACP in AA. That AA appear to prefer informal discussions about ACP to formal documentation of preferences suggests that future research should focus on improving ACP conversations among clinicians, patients, and their families in order to improve the receipt of goal-concordant care at EOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(141 citation statements)
references
References 84 publications
7
126
3
1
Order By: Relevance
“…In concordance with the health care literature, EOL decisions made by caregivers were not autonomous (i.e., independent acts) but instead family-centered and involved communication with health care providers as a resource. These findings are consistent with those of other recently published literature (Sanders, Robinson, & Block, 2016; Smith-Howell, Hickman, Meghani, Perkins, & Rawl, 2016), and serve as a reminder for health care providers to focus on the specific needs of the individual and family when using EOL terminology. Moreover, heavy reliance is placed on health care providers' (mainly nurses and physicians) input regarding EOL decision making, emphasizing the need for health care providers to be sensitive to the needs of individuals and families within cultural contexts.…”
Section: Discussionsupporting
confidence: 91%
“…In concordance with the health care literature, EOL decisions made by caregivers were not autonomous (i.e., independent acts) but instead family-centered and involved communication with health care providers as a resource. These findings are consistent with those of other recently published literature (Sanders, Robinson, & Block, 2016; Smith-Howell, Hickman, Meghani, Perkins, & Rawl, 2016), and serve as a reminder for health care providers to focus on the specific needs of the individual and family when using EOL terminology. Moreover, heavy reliance is placed on health care providers' (mainly nurses and physicians) input regarding EOL decision making, emphasizing the need for health care providers to be sensitive to the needs of individuals and families within cultural contexts.…”
Section: Discussionsupporting
confidence: 91%
“…However, the ways preferences produce care decisions are not monoculturally formulaic. 46 For example, advance directives are one way that individuals express their preferences, but some studies have concluded that AAs prefer informal end-of-life planning based on personal relationships with their community leaders and clinicians to formal documentation of preferences in advance directives. 47 Studies conclude that this could be related to distrust due to mistreatment; poor communication with practitioners; historic patterns of slavery, racism, and research abuses; and faith that emphasizes giving control to a higher power, but taking personal responsibility for doing what is possible.…”
Section: Preferences For Carementioning
confidence: 99%
“…52 In a range of different contexts, there were calls for further exploration of patient and carer understandings of ACP, understandings of patients' illnesses and their end-of-life wishes, and how family relationships affect decision making. 31,32,55,59,72,75 Research on ACP for individuals with intellectual disabilities will need to overcome the methodological complexities in involving this group. 33,34 Other reviews focused on intervention development and evaluation, particularly on formats and timing of ACP.…”
Section: Recommendations For Researchmentioning
confidence: 99%